Jual Beli Jabatan Sebagai Area Rawan Korupsi Menggangu Reformasi Birokrasi - Amalia Syauket; Kardinah Indrianna Meutia (Jurnal Hukum Sasana, 2023)
Pejorative language that all matters must be cash, although it is painful but very appropriate to describe the condition of public services in the era of regional autonomy which is still not optimal, including in the procurement of the State Civil Apparatus. The phenomenon of the still rampant sale and purchase of positions and trading of influence is very different from the demands and dynamics of society which lead to digitization of service administration and transparency. This gap creates opportunities for paid public services, including the appointment of high-ranking officials in government. The bureaucracy must be paid so that it runs and moves according to the wishes of the people. This all-paid condition greatly disrupts the course of bureaucratic reform which was proclaimed since 2004 with the main pillar of good & clean governance. The area for buying and selling positions is an area prone to corruption by regional heads. This study aims to find out, what causes the practice of buying and selling positions to be rampant? The results of the study show that the main cause of the rampant buying and selling of positions is because the employee selection process is carried out in a closed manner (non-meritocracy) and there is political intervention in the management of the State Civil Apparatus, for example in filling positions. family, and political relations.